1982
DOI: 10.1139/m82-108
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional iron status and susceptibility to Proteus mirabilis pyelonephritis in the rat

Abstract: Moderately iron-deficient rats were significantly less susceptible to experimentally induced Proteus mirabilis pyelonephritis than iron-sufficient or severely iron-deficient littermates, as indicated by significantly lower prevalence of infection, mean pyelonephritic lesion scores, and numbers of P. mirabilis cells recovered from the kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…However our results confirm those reported by other investigators for S. typhimurium (15) and other bacteria (7,9,20), showing increased resistance of hypoferremic animals to bacterial infection. Generally, protein malnutrition increases host susceptibility to infection as a result of the depression of nonspecific resistance factors and alteration of humoral and cellmediated immunity (6,13,14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However our results confirm those reported by other investigators for S. typhimurium (15) and other bacteria (7,9,20), showing increased resistance of hypoferremic animals to bacterial infection. Generally, protein malnutrition increases host susceptibility to infection as a result of the depression of nonspecific resistance factors and alteration of humoral and cellmediated immunity (6,13,14).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless other investigators have shown that laboratory animals fed an iron-deficient diet had decreased serum iron levels but increased resistance to various experimental infections (9,15). Such results are in agreement with the observation that lowering of the plasma iron content is a physiological reaction against infection (20).…”
mentioning
confidence: 99%
“…All P. vulgaris strains showed this haemolytic activity but at a significantly lower level than the P. mirabilis strains; it is a strongly cell-associated property (Peerbooms et al, 1983). The possible role of haemolysin production in the pathogenesis of urinary-tract infections could be the liberation of iron compounds (Waalwijk, MacLaren and De Graaf, 1983) stimulating bacterial growth in vivo (Hart, Kadis and Chapman, 1982), creation of favourable growth conditions by cell destruction or stimulation of cell invasiveness. This latter phenomenon we described earlier for P. mirabilis (Peerbooms et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins involved in iron acquisition are critical virulence factors produced during a UTI (9,42,45,457) and, potentially, CAUTIs, since this nutrient is limiting in urine (363). The addition of exogenous iron reduces the susceptibility of animals to the development of P. mirabilis pyelonephritis (131). While most enterobacteria produce phenolate (enterobactin)-and/or hydroxamine (aerobactin)-type siderophores during iron-limiting conditions (42,45,296), none of these traditional siderophores have been demonstrated to be produced in Proteus, Providencia, or Morganella species (92,296,323).…”
Section: Damage To the Host And Acquisition Of Nutrientsmentioning
confidence: 99%